Diálogos sobre a proposta de formação do programa de alfabetização na idade certa (PAIC) - Costa, Mônica Cristina Medici da (2021)
This research is aimed at understanding the pedagogical proposal of the Pact for Literacy at the Right Age (Paic) of the State of Ceará regarding the conceptions of language, literacy and literacy that underlies the formation of literacy teachers. It is characterized as documentary research, focusing on the Pedagogical Didactic Proposal to Literate Literacy, as well as the activities of the four stages that make up the magazine “Vamos Passear na Escrita,” aimed at 1st year children, also called Activity Book. In this investigative path, academic-scientific productions about the theme were part of our study. The research came from the thesis that, despite being announced by the author that the objective of the proposal of Literacy and Initial Reading Instruction is in accordance with the declarative discourse, with Bakhtin concepts and some of the authors that worked with Bakhtin and with the psychogenesis of the written language (the ferreirian constructivism). The teaching model of the didactic proposal of Literacy and Initial Reading Instruction of Paic is set on the pillars of the theory of constructivism. Consider how the theoretical and methodological principals, the Bakhtin approach in the field of Philosophy of language, as well as the historical and cultural studies in the field of Psychology conclude that Paic demonstrates a guideline for the politics of formation continued by professors of literacy that defends constructivism. In this context, in addition to teaching teachers that children go through predetermined steps while they are learning to read and write, it also teaches language from abstract forms, with no connection to life.